Hypotheses relating to the function of the claustrum - Smythies, John; Edelstein, Lawrence; Ramachandran, Vilayanur (Frontiers in Integrative Neuroscience, 2012)
This paper present a new hypothesis as to the function of the claustrum. Our basic premise is that the claustrum functions as a detector and integrator of synchrony in the axonal trains in its afferent inputs. In the first place an unexpected stimulus sets up a processed signal to the sensory cortex that initiates a focus of synchronized gamma oscillations therein. This focus may then interact with a general alerting signal conveyed from the reticular formation via cholinergic mechanisms, and with other salient activations set up by the stimulus in other sensory pathways that are relayed to the cortex. This activity is relayed from the cortex to the claustrum, which then processes these several inputs by means of multiple competitive intra-claustral synchronized oscillations at different frequencies. Finally it modulates the synchronized outputs that the claustrum distributes to most cortical and many subcortical structures, including the motor cortex. In this way, during multicenter perceptual and cognitive operations, reverberating claustro-cortical loops potentiate weak intracortical synchronizations by means of connected strong intraclaustral synchronizations. These may also occur without a salient stimulus. By this mechanism, the claustrum may play a strong role in the control of interactive processes in different parts of the brain, and in the control of voluntary behavior. These may include the neural correlates of consciousness. We also consider the role of GABAergic mechanisms and deafferentation plasticity.